2019
DOI: 10.7717/peerj.7094
|View full text |Cite
|
Sign up to set email alerts
|

How glyphosate and its associated acidity affect early development in zebrafish (Danio rerio)

Abstract: Background Glyphosate is among the most extensively used pesticides worldwide. Following the ongoing highly controversial debate on this compound, its potential impact on non-target organisms is a fundamental scientific issue. In its pure compound form, glyphosate is known for its acidic properties. Methods We exposed zebrafish (Danio rerio) embryos to concentrations between 10 μM and 10 mM glyphosate in an unbuffered aqueous medium, as well as at pH 7, for 96 hours post fertilization (hpf). Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Another recent study on pharmaceuticals in the zebrafish embryo assay showed higher toxicity with higher fraction of neutral species (Alsop and Wilson ). We did not include a study on the pH‐dependent toxicity of glyphosate toward zebrafish embryos in Supplemental Data, Table S1, because the zebrafish embryo assay was performed unbuffered and pH was <4, most likely leading to pH effects rather than effects of glyphosate because glyphosate did not cause any mortality up to 10 mM when buffered to pH 7 and the negative control was almost equally toxic at low pH values (Schweizer et al ).…”
Section: Ph Dependence Of Aquatic Toxicity Of Iocsmentioning
confidence: 99%
“…Another recent study on pharmaceuticals in the zebrafish embryo assay showed higher toxicity with higher fraction of neutral species (Alsop and Wilson ). We did not include a study on the pH‐dependent toxicity of glyphosate toward zebrafish embryos in Supplemental Data, Table S1, because the zebrafish embryo assay was performed unbuffered and pH was <4, most likely leading to pH effects rather than effects of glyphosate because glyphosate did not cause any mortality up to 10 mM when buffered to pH 7 and the negative control was almost equally toxic at low pH values (Schweizer et al ).…”
Section: Ph Dependence Of Aquatic Toxicity Of Iocsmentioning
confidence: 99%
“…Glyphosate and commercial products (e.g. RoundUp) made with glyphosate have been repeatedly reported to cause embryo mortality and deformations in fish (zebrafish 10uM to 1 mM pure glyphosate 9 , 10 mg/L RoundUp or pure glyphosate 10 ), and aquatic amphibians (Xenopus 0.3-1.3 mg/L RoundUp 11 , 500 pg/egg pure glyphosate 12 ). In contrast, mammal and bird embryos and fetuses are exposed to glyphosate residues only via maternal transfer of the chemicals, which may result in malformations, altered sex ratios, and low sperm quality in rodent models (doses: 500 mg/kg RoundUp 13 , 5 g/L pure glyphosate 14 , 50-450 mg/kg RoundUp 15 ).…”
mentioning
confidence: 99%
“…In field studies, the half-life of glyphosate can range between a few days to around 6 months [ 50 ]. In soils, glyphosate competes with phosphorus and thus its absorption depends on mineral composition [ 51 ]. All these environmental factors will impact GBH availability to earthworms in agricultural settings.…”
Section: Resultsmentioning
confidence: 99%